Cystic echinococcosis (Hydatidosis) in sheep , goats, cattle and camels in Shahat Abattoir Al-Jabal Al- Akhdar - Libya. - Al- khalidi, Nahad Walli (Al-Mukhtar Journal of Sciences, 1998)
An infection rate of 8.4% with Cystic echinococcosis (Hydatidosis) was recoverd among 1050 sheep, goats, cattle and camels in Shahat Abattoir in Al- Jabal Al- Akhdar Libya. Of 554 sheep , 48 (8.7%) sheep were infected, of 338 goats, 18 (5.4%) goats were infected. of 124 cattle , 8 (6.4%) cattle were infected and of 40 camels , 14 (35%) camels were infected. The animals were of both sexes and of various ages. The infection of 87.2% of infected sheep was in the liver , 33.4% was in the lungs , 6.3% was in the peritoneal cavity, and 2.4% was in the spleen. Meanwhile the infection of 61.0% of infected goats was in the liver , 55.5% was in the lungs and 5.5% was in each of the spleen and the kidneys. As of the infection of cattle , 75.0% of the infection was in the liver, 37.5 was in the lungs and 12.5% was in the spleen . In camels however, most of the infection 78.5% was in the lungs and only 35.7% was in the liver, with only a single case (7.1%) the infection of which was in the heart. There were also many mixed infection cases. The cysts of all infected cattle , but one cow (12.5%), were sterile, while the cysts of the other animals were mostly fertile. The fertility rate of sheep cysts was 79.2% of goats was 61.0% and of camels was 57%.